GCPII and its close homolog GCPIII: from a neuropeptidase to a cancer marker and beyond - Vorlova, Barbora; Knedlik, Tomas; Tykvart, Jan; Konvalinka, Jan (Frontiers in bioscience (Landmark edition), 2019)
Glutamate carboxypeptidases II and III (GCPII and GCPIII) are highly homologous di-zinc metallopeptidases belonging to the M28 family. These enzymes are expressed in a variety of tissues, including the brain, prostate, kidney, testis and jejunum. GCPII has been recognized as a neuropeptidase in the central nervous system, as a folate hydrolase participating in absorption of folates in the jejunum and, most importantly, as a prostate-specific membrane antigen that is highly expressed in prostate adenocarcinoma. Furthermore, it has been identified in the neovasculature of most human solid tumors. In contrast, GCPIII has not been associated with any specific physiological function or pathology, and its expression, activity and inhibition have not been as well-studied. In this review, we provide an overview of the current understanding of the structure, enzymatic activity, substrate specificity, and tissue distribution of these two homologous enzymes. We discuss their potential physiological functions and describe the available animal models, including genetically modified mice. We also review the potential use of specific monoclonal antibodies and small-molecule inhibitors recognizing GCPII/III for diagnosis, imaging and experimental therapy of human cancers and other pathologies.
Keywords: Prostatic Neoplasms; Adenocarcinoma; Hydrolysis; nádory prostaty; mutantní kmeny myší; mozek; karboxypeptidasy; Humans; Neuropeptides; Mice, Transgenic; glutamáty; hydrolýza; Peptide Hydrolases; Biomarkers, Tumor; glutamátkarboxypeptidasa II; jejunum; Antibodies, Monoclonal; Antigens, Surface; myši transgenní; tenké střevo; Phenotype; antigeny povrchové; krysa rodu Rattus; Inflammatory Bowel Diseases; kyselina asparagová; lidé; Jejunum; zvířata; myši; Glutamates; neuropeptidy; Mice; nádorové biomarkery; Intestine, Small; idiopatické střevní záněty; Male; Brain; fenotyp; monoklonální protilátky; Rats; Glutamate Carboxypeptidase II; adenokarcinom; Mice, Mutant Strains; Animals; Aspartic Acid; Carboxypeptidases; mužské pohlaví; Disease Models, Animal; proteasy; modely nemocí na zvířatech